1995
DOI: 10.1109/7.395235
|View full text |Cite
|
Sign up to set email alerts
|

On deflection as a performance criterion in detection

Abstract: The performance of detection system is usually characterized by the receiver operating characteristics (ROC) curves. Because of the complexity of the calculation of such curves simpler performance criteria are useful. Among these, the deflection criterion, or output signal-to-noise ratio, is one of the most interesting. The advantages and limitations of the deflection are first analyzed. Attention is especially paid to the relation between singular detection and S i n i t e deflection Maximization of the defle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
83
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 120 publications
(83 citation statements)
references
References 6 publications
0
83
0
Order By: Relevance
“…There are other measures of performance such as output signal to noise ratio, or de ection criterion (36) , but the AUC seems to be the only one that is independent of the decision threshold and not biased by prior probabilities.…”
Section: The Standard Error Of Aucmentioning
confidence: 99%
“…There are other measures of performance such as output signal to noise ratio, or de ection criterion (36) , but the AUC seems to be the only one that is independent of the decision threshold and not biased by prior probabilities.…”
Section: The Standard Error Of Aucmentioning
confidence: 99%
“…Under Gaussian assumptions, it is known that maximizing the deflection coefficient leads to the maximization of the detection performance in terms of the ROC curve [31]. In fact, it can be shown that for the centralized shift-in-mean Gaussian detection problem, the ROC curve in (19) could be expressed as [30] …”
Section: Measurement Of Detection Performancementioning
confidence: 99%
“…as a performance criterion due to its simplicity and its strong relationship with the actual overall detection performance [13].…”
Section: B Sr Employed At the Fcmentioning
confidence: 99%